Complex Dynamic Systems Theory in Second Language Acquisition: Exploring Concepts and Unpacking Constructs - Shan An; Ashley Beccia (Studies in Applied Linguistics & TESOL)
In January 2000, Stephen Hawking predicted, “the next century will be the century of complexity” (Sanders, 2003). Indeed, complexity science, or the study of the structure and behavior of complex dynamic systems, has become increasingly popular as researchers aim to understand the complexity that surrounds us – e.g., rainforests, immune systems, the global economy, and language (Sanders, 2003). In fact, at the time that Stephan Hawking made his prediction, complexity science and systems thinking had already permeated numerous disciplines, including, and of particular interest to the current forum, second language acquisition (SLA).